2019
DOI: 10.1039/c9ra05404a
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic CO2 adsorption of polyethylene polyamine-loaded MCM-41 before and after methoxypolyethylene glycol codispersion

Abstract: To reduce the cost of CO2 capture, polyethylene polyamine (PEPA), with a high amino density and relatively low price, was loaded into MCM-41 to prepare solid sorbents for CO2 capture from flue gases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Shafawi et al (2021) have mentioned that the presence of N-functional groups will increase the surface basicity and polarity of the aminefunctionalized biochar, thus strengthening the adsorption of CO 2 molecules. This statement also agrees well with research work by Wang et al (2019), which also stated that nitrogen amount is frequently cited as the primary variable affecting the selectivity of CO 2 adsorption in carbon sorbents. Thus, this result q e q t k 2…”
Section: Selectivitysupporting
confidence: 92%
“…Shafawi et al (2021) have mentioned that the presence of N-functional groups will increase the surface basicity and polarity of the aminefunctionalized biochar, thus strengthening the adsorption of CO 2 molecules. This statement also agrees well with research work by Wang et al (2019), which also stated that nitrogen amount is frequently cited as the primary variable affecting the selectivity of CO 2 adsorption in carbon sorbents. Thus, this result q e q t k 2…”
Section: Selectivitysupporting
confidence: 92%
“…However, the amount of N 2 sorbed by the modified samples decreases as a result of the amine group being an N 2 donor, which cannot adsorb more N 2 molecules since they are like charges (like charges repel). However, they have been reported to have a high affinity for CO 2 because it is an unlike charge that they can attract due to electrostatic forces [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…In spite of the relatively good adsorption performance for the grafted and impregnated porous sorbents, the low amine contents of aminosilanes and the agglomeration and weak volatility of liquid amines limited the adsorption capacity or amine efficiency. Thus, a combined method of either first grafting then impregnation was adopted [ 30 , 31 , 32 ], otherwise the additives were added during the impregnation of liquid amines into the supporting materials [ 33 , 34 , 35 , 36 , 37 ]. Sanz et al synthesized the pore-expanded MCM-41-based sorbents, respectively, by grafting with aminosilane of aminopropyl orethylenediamino, impregnating with liquid amine of PEI or tetraethylenepentamine (TEPA), and a double functionalization method of first grafting with aminosilane then impregnating with organic amine; the results showed that their corresponding maximum CO 2 adsorption capacity were respectively 1.75, 2.20 and 2.36 mmol/g, with amine efficiency separately being 0.38, 0.25 and 0.37 mol CO 2 /mol N, and a double functionalization method improved the dispersion and exposure of viscous amine [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, the polyetheramine of poly(propylene glycol)bis(2-aminopropyl ether) (A) was chosen as the additive, and coimpregnated with TEPA into MCM-41 to prepare the composite CO 2 sorbents [ 33 ]. Due to the high electron cloud density around the O atoms in A and good dispersion of TEPA in pore channels, the composites exhibited not only good physisorption at 30 °C and ideal chemisorption at 60 °C, but also high desorption efficiency; methoxypolyethylene glycol (MPEG) was codispersed and coimpregnated with PEPA to prepare composite sorbents for CO 2 capture, in which the adsorption capacity and regeneration performance were improved with respect to that of PEPA-impregnated MCM-41 [ 35 ].…”
Section: Introductionmentioning
confidence: 99%